(untitled) (Zaporizhzhia Historical Review, 2021)
The historiographical achievements concerning social and political organizations of Ukrainian southern region at the end XIX-th – the beginning of XX-th century are analyzed in the article. The author comes to the conclusion that problem of researched societies functioning of stated period demands further study.